The classic "brown-ring" reaction in a new medium: kinetics, mechanism, and spectroscopy of the reversible binding of nitric oxide to iron(II) in an ionic liquid. - Begel, Svetlana; Heinemann, Frank Wilhelm; Stopa, Grzegorz; Stochel, Grazyna; van Eldik, Rudi (Inorganic Chemistry, 2011)
To elucidate the applicability and properties of ionic liquids (ILs) to serve as chemical reaction media for the activation of small molecules by transition-metal complexes, detailed kinetic and mechanistic studies were performed on the reversible binding of NO to FeCl(2) dissolved in the IL 1-ethyl-3-methylimidazolium dicyanamide ([emim][dca]) as a solvent. We report, for the first time, the application of laser flash photolysis at ambient and high pressure to study the kinetics of this reaction in an IL. The kinetic data and activation parameters for the "on" and "off" reactions suggest that both processes follow a limiting dissociative (D) ligand substitution mechanism, in contrast to that reported for the same reaction in aqueous solution, where this well-known "brown-ring" reaction follows an interchange dissociative (I(d)) ligand substitution mechanism. The observed difference apparently arises from the participation of the IL anion as a N-donor ligand, as evidenced by the formation of polymeric [Fe(dca)(3)Cl](x)[emim](2x) chains in the solid state and verified by X-ray crystallography. In addition, infrared (IR), Mössbauer, and EPR spectra were recorded for the monomeric reaction product [Fe(dca)(5)NO](3-) formed in the IL, and the parameters closely resemble those of the FeNO(7) unit in other well-characterized nitrosyl complexes. It is concluded that its electronic structure is best described by the presence of a high-spin Fe(III) (S = 5/2) center antiferromagnetically coupled to NO(-) (S = 1), yielding the observed spin quartet ground state (S(t) = 3/2).